KEWIRAUSAHAAN MAHASISWA DI IAIN LAMPUNG - Dermawan, Oki (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2013)
Entrepreneurship provide many benefits for students such as: 1. Creative thinking skills, combining imagination with scientific thinking skills, 2. Skills in Decision Making, at any time during the life one has to hold elections among alternatives, 3. Leadership skills . learn to have a strong personality , then someone will have the skills to lead yourself . 4 . Managerial skills, however, entrepreneurs must be able to manage all resources , both material resources and personnel to achieve success . skilled in planning , skilled in organizing , entrepreneurial guidance may hold or control, is able to conduct an assessment of the implementation, 5.Interpersonal skills or Human relations. Theoretical approach are given to students with a practical approach should be replaced, because the public wants a business man, not bisnis expert, and should be doing. informal coaching , which is important in this process is the formation of entrepreneurial character, with informal coaching will more effective in shaping a person’s character than formal guidance that predominantly affects IQ.